Development of Prezi-Based KOH Link Learning Media in Elementary School Science Lessons - Kasmawati Kasmawati; Yuni Permata Sari; Ashari Usman; Chairan Zibar L Parisu; La Sisi; Arna Juwariyah (Jurnal Penelitian Pendidikan IPA, 2023)
The background of this research is because the Prezi application-based KOH Link learning media has not yet been developed in science learning. In the learning process, the teacher already uses learning media but is less creative, while at school the facilities and infrastructure are adequate, such as LCD projectors. This study aims to determine the process of developing prezi-based KOH Link learning media products, to determine the level of effectiveness of learning media. This type of research is research and development (research and development) of the Four-D model which consists of defining, designing, developing, and disseminating. Data collection techniques are carried out by carrying out effectiveness. Data analysis techniques are performed by calculating the average value of the results of effectiveness. The results showed that classical completeness was 81.48% with very good criteria and student responses obtained an average of 3.7 with very positive criteria. Thus, it can be concluded that the Prezi-based KOH Link learning media in classifying animals based on the type of food is very effective as one of the media in science subjects.